1999
DOI: 10.1023/a:1007128008153
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We suggest that transrectal ultrasound-guided seminal vesicle biopsy is useful and reliable for a more exact preoperative staging of prostate cancer, therefore helpful in correct decision making for radical prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Seminal vesicle invasion is an insufficient prognostic parameter with biochemical progression- free rates varying between 5–60% [ 42 , 43 ]. Bloom et al showed the relation between SVI and post radical prostatectomy high BCR levels which later developed distant metastasis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seminal vesicle invasion is an insufficient prognostic parameter with biochemical progression- free rates varying between 5–60% [ 42 , 43 ]. Bloom et al showed the relation between SVI and post radical prostatectomy high BCR levels which later developed distant metastasis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%